Supportive initiatives of Brussels based stakeholders - Vosečková, Anna (Univerzita Pardubice, 2014)
The presentation will provide information on services and activities of the Czech Liaison Office for Research, Development and Innovation (CZELO) in Brussels. The intensive environment in which the CZELO staff is working will be introduced as well. It includes not only the partner liaison offices, but also Brussels offices of many European and international companies, associations, organizations, groupings etc. Last but not least, the cooperation with the representatives of the European institutions.
Keywords: research; innovation; education; cooperation; support to Czech researchers